The Role of Public Secondary Schools' Principal's in the Development of the Local Community in the Northern West Bank from the Viewpoint of Fathers and Mothers Councils - Rafeef Marwan Taher Izgheibi (My University, 2014)
This study aimed to identify the role of principals of public secondary schools in developing the local community in the northern West Bank governorates from the points of view of the Paent Teacher Association ( BTA) councils , also aimed to identify the impact of the study variables ( gender, academic achievement , family income , the nature of the work , and place of residence) to the responses degree of the ( BTA) councils for the role of principals of public secondary schools in community development in governorates of the northern West Bank . The study population consisted of ( 2541 ), a members of mothers and fathers councils, ( 1176 ) is males , and ( 1365 is females , according to personnel records at the Palestinian Ministry of Education and Higher Education of the first semester of 2013 / 2014. The researcher used the descriptive method. The study sample was chosen as a stratified random sample , and the researcher identified governorates in northern Palestine surveyed, so that the study was conducted on the members of the parents councils in public secondary schools in the governorates of the northern West Bank and the number was ( 254 ), a member members of mothers and fathers, a rate of (10 %) of the population of the study . In order to achieve the objectives of this study, the researcher prepared a questionnaire consisting of (46) paragraphs divided into 4 fields , developing local community , developing family development , developing governmental institutions , developing civil institutions according to the Likert scale. To answer the first question, the averages and percentages were extracted for each paragraph, each field, and for the total degree of the tool. To examine the questions and hypotheses of the study, the following tests were used: One Sample T-test, T – test for independent groups, analysis of variance (ANOVA), Scheffe - post hoc Test. The most important findings of the study: - The degree of councils parents responses at the members of mothers and fathers councils for the role of principals of public secondary schools in community development in governorates of the northern West Bank was large . - There was no statistically significant differences at the significance level (α = 0.05) in the average responses of the members of mothers and fathers councils for the role of principals of public secondary schools in community development in governorates of the northern West Bank due to the gender, academic achievement , family income, and the nature of work in the fields of developing community , developing family and government institutions . - There were statistically significant differences at the significance level (α= 0.05) in the average responses of the members of mothers and fathers councils for the role of principals of public secondary schools in community development in governorates of the northern West Bank due to the variable nature of work in the field of the role of the principal of the school in developing family and the overall field in favor of government job , compared with special functions or otherwise . - There were statistically significant differences at the significance level (α= 0.05) in the average responses of the members of mothers and fathers councils for the role of principals of public secondary schools in community development in governorates of the northern West Bank due to the variable place of residence were these differences in Salfit , compared with the other governorates of the northern West Bank. The most important recommendations of the study : • Find a good and cooperative relationship between the principals ,school teachers and the local community with various institutions. • Reduce the burden of principals and school teachers in order to get ( to achieve ) better community shares. • Rework the relationship between the school boards and parents in order (to create ) a better communication among them. • More attention by school principals to find the suitable time to arrange the meetings with the members of mothers and fathers councils and the local community institutions.

هدفت هذه الدراسة إلى التعرف لدور مديري المدارس الحكومية الثانوية في تنمية المجتمع المحلي في محافظات شمال الضفة الغربية في فلسطين من وجهات نظر مجالس الآباء والأمهات، كما هدفت للتعرف إلى أثر متغيرات الدراسة (الجنس، والمؤهل العلمي، ودخل الأسرة، وطبيعة العمل، ومكان السكن) في درجة استجابات أعضاء مجالس الآباء والأمهات إلى دور مديري المدارس الحكومية الثانوية في تنمية المجتمع المحلي في محافظات شمال الضفة الغربية. وقد تكون مجتمع الدراسة من (2541) عضو لمجالس الآباء والأمهات، منهم (1176) عضو من الذكور، و(1365) عضو من الإناث، وذلك حسب سجلات شؤون الموظفين في وزارة التربية والتعليم العالي الفلسطينية للفصل الدراسي الاول 2012م/ 2013م. وقد استخدمت الباحثة المنهج الوصفي، إذ تم اختيار عينة الدراسة بصورة العينة العشوائية وحددت الباحثة المحافظات الفلسطينية في شمال الضفة الغربية في فلسطين التي شملتها الدراسة، بحيث أجريت الدراسة على أعضاء مجالس الآباء والأمهات في المدارس الثانوية الحكومية في محافظات شمال الضفة الغربية وكان عددهم من ( 254 ) عضو من أعضاء مجالس الآباء والأمهات، أي ما نسبته ( 10 %) من مجتمع الدراسة. ومن أجل تحقيق أهداف هذه الدراسة أعدت الباحثة استبانه مكونة من (46) فقرة مقسمة على 4 مجالات هي، تنمية البيئة المحلية، وتنمية الأسرة ، وتنمية المؤسسات الحكومية، وتنمية المؤسسات الأهلية. ومقياسًا لتقدير درجة الاستجابة تم استخدام سلم ليكرت الخماسي. للإجابة عن أسئلة وفرضيات الدراسة تم استخراج المتوسطات الحسابية والنسب المئوية لكل فقرة، ولكل محور، وللدرجة الكلية للأداة، كما تم استخدام اختبار (One Sample T-test) واختبار (ت) للمجموعات المستقلة Independent T- test) ) ، وتحليل التباين الأحادي ( ANOVA )، واختبارات شفيه للمقارنات البعدية (Scheffe - post hoc Test). أهم النتائج التي توصلت إليها الدراسة: • أن درجة استجابة أعضاء مجالس الآباء والأمهات في مديريات التربية والتعليم لمحافظات شمال الضفة الغربية لدور مديري المدارس الحكومية الثانوية في تنمية المجتمع المحلي من وجهات نظر أفراد العينة كانت كبيرة . • لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05=α) في متوسط استجابات أعضاء مجالس الآباء والأمهات لدور مديري المدارس الحكومية الثانوية في تنمية المجتمع المحلي في محافظات شمال الضفة الغربية تعزى لمتغير الجنس، والمؤهل العلمي، دخل الأسرة، وطبيعة العمل في مجالات تنمية البيئة المحلية والأسرة والمؤسسات الحكومية. • توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05=α) في متوسط استجابات أعضاء مجالس الآباء والأمهات لدور مديري المدارس الحكومية الثانوية في تنمية المجتمع المحلي في محافظات شمال الضفة الغربية تعزى لمتغير طبيعة العمل في مجال دور مدير المدرسة في تنمية الأسرة والمجال الكلي لصالح الوظيفة الحكومية بالمقارنة مع الوظائف الخاصة أو غير ذلك. • توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05=α) في متوسط استجابات أعضاء مجالس الآباء والأمهات لدور مديري المدارس الحكومية الثانوية في تنمية المجتمع المحلي في محافظات شمال الضفة الغربية تعزى لمتغير مكان السكن وكانت هذه الفروق في محافظة سلفيت بالمقارنة مع محافظات شمال الضفة الأخرى. أهم توصيات الدراسة: • تشكيل فرق تطوير مدرسي وفرق تطوير مجتمع محلي يتكون من أعضاء من المدرسة وأعضاء من المجتمع المحلي بحيث تكون الفائدة أكبر. • تخفيف الأعباء المدرسية عن كاهل مديري المدارس والمعلمين من أجل مشاركات مجتمعية أفضل. • إعادة صياغة العلاقة بين المدرسة ومجالس الآباء والأمهات من أجل تواصل أفضل فيما بينهم. • الاهتمام من قبل الإدارات المدرسية بتوقيت مناسب للاجتماعات سواء مع مجالس الآباء والأمهات ومؤسسات المجتمع المحلي.
دور مديري المدارس الحكومية الثانوية في تنمية المجتمع المحلي في محافظات شمال الضفة الغربية في فلسطين من وجهات نظر مجالس الآباء والأمهات